Multiple Dermal Abscesses by Trichophyton rubrum in an Immunocompromised Patient - Toussaint, Frédéric; Sticherling, Michael (Frontiers in Medicine, 2019)
We report the case of a 52-year-old man who presented with a 10 year history of multiple nodules with purulent drainage on the upper extremities. Several attempts of treatment with oral antibiotics had been unsuccessful. A skin biopsy specimen showed a dermal abscess with branched septate hyphae. A mycological culture of pus and of the biopsy specimen revealed Trichophyton rubrum. Deeper dermatophytosis presenting as dermal abscesses is a rare disease which occurs normally in immunocompromised conditions. Our patient was on immunosuppressive therapy with methylprednisolone and azathioprine because of inflammatory demyelinating polyneuropathy and presented with extensive abscesses. In cases of dermal abscesses it is important to not only consider bacterial but also fungal infections as underlying cause.